Determination of immune status in dogs against CPV-2 by recombinant protein based latex agglutination test. (September 2017) - Thomas, Jobin; Singh, Mithilesh; Goswami, T.K.; Glora, Philma; Chakravarti, Soumendu; Chander, Vishal; Upmanyu, Vikramaditya; Verma, Suman; Sharma, Chhavi; Mahendran, K.
Abstract: Canine parvoviral enteritis is a highly contagious viral illness caused by canine parvovirus-2 (CPV-2) which affects puppies of mainly 6–20 weeks of age. Vaccination is pivotal in preventing and controlling CPV-2 infection. Determination of antibody status is a critical determinant for successful vaccination. The hemagglutination inhibition (HI) test is 'gold standard' test for quantification of antibodies specific to CPV-2, although the execution of this test is not feasible under field conditions. The present study was undertaken to develop a point of care testing to determine immune status prior to CPV-2 vaccination or to detect seroconversion in immunized dogs by latex agglutination test (LAT) using recombinant antigen. Truncated portion of VP2 protein (tVP2) of CPV-2 was selected on the basis of antigenic indices, overexpressed the recombinant protein in E. coli system and was subsequently used in development of LAT. A total of 59 serum samples obtained from vaccinated (n = 54) and healthy unvaccinated (n = 5) dogs were tested. The positivity was observed in 85% (46/54) of these dogs with varying agglutination pattern. The overall sensitivity and specificity of latex agglutination test in comparison to HI test was recorded as 90% and 88% respectively with an agreement value of 90% (CI = 95%). Highlights: Latex agglutination test based on recombinant VP2 protein of CPV-2 is proposed. The test has 90% sensitivity and 88% specificity in comparison to gold standard HI test. This is a rapid and simple immunoassay to determine the immune status of dogs against CPV-2 infection.